Preventing lead release from perovskites - Hoye, RLZ (Springer Nature, 2023)
Lead-halide perovskites could revolutionize the provision of low-cost solar energy but are limited by their neurotoxic lead content, which can readily dissolve in water. A supramolecular complex has now been developed to suppress lead release.